IMPROVING TEACHERS' TRANSFORMATIVE TEACHING SKILLS IN DELIVERING ENGLISH LESSONS THROUGH A TASK-BASED MENTORING PROGRAM AT SD SYARIF AR RASYID IN MEDAN - Ariatna, Ariatna; Nazlah Syahaf Nasution; Ita Khairani (Bajang Institute, 2024)
SD Syarif Ar Rasyid, a private elementary school in Medan, has 11 teachers and 86 students. With the adoption of Kurikulum Merdeka in the 2023-2024 academic year, teachers are required to implement transformative teaching, which emphasizes student-centered learning. However, the transition has been challenging due to limited collaboration among teachers and lack of access to transformative teaching resources, especially for English lessons. This community service program aims to improve teachers' transformative teaching skills in English through a Task-Based Mentoring (TBM) program. The program includes training, developing task-based learning materials, and establishing a teacher learning community. Expected outcomes include reports, journal publications, media coverage, and intellectual property rights for the program materials. The program uses a mixed-methods approach, focusing on needs analysis, training, material development, mentoring, evaluation, and community building to enhance teaching quality.